The Impact of Industry 4.0 on the Economy - Hannah Fawna (GoAcademica Research & Publishing, 2023)
This journal article examines the influence of Industry 4.0 on the economy, exploring its key components and potential benefits. Industry 4.0, also known as the Fourth Industrial Revolution or the Digital Revolution, entails the integration of digital technologies into various industries. The article investigates how this transformation is reshaping production processes, workforce dynamics, and business models, ultimately driving economic growth and innovation. Moreover, it addresses the challenges and implications of Industry 4.0 to provide a comprehensive understanding of its effects on the economy.